Physico-chemical and microalgal gradients change rapidly in response to mouth closure in a predominantly open estuary. Issue 1 (2nd April 2020) - Lemley, DA; Adams, JB
Abstract : A third of South Africa's freshwater flow no longer reaches the coast, yet few systems have shifted from being permanently open to temporarily closed. For the first time since 1969, the Gamtoos Estuary mouth closed in June 2018, because of extensive drought conditions and freshwater abstraction. Accordingly, physico-chemical gradients, microalgal biomass and species composition were sampled during low (closed mouth), normal (open mouth) and high (breaching event) flow conditions. The closed phase was characterised by polyhaline and homogenous salinity structures and a rapid shift towards eutrophic conditions, as evidenced by bottom water hypoxia (<2 mg l −1 ), elevated phytoplankton (>20 μg l −1 ) and microphytobenthos (>100 mg m −2 ) biomass, and proliferation of a harmful algal bloom (HAB) species ( Prorocentrum cordatum, Dinophyceae). An artificial breaching event in September 2018 restored connectivity with the marine environment and within a month re-established the usual physico-chemical gradients that characterise the open phase. Although the current study demonstrates ecosystem recovery from stochastic events, it also highlights the potential impact (e.g. HABs, hypoxia) of shifting an estuary into a new stable state. This is a concern given that mouth closure events in South African estuaries are likely to increase in the future in response to global change pressures.